The genetic variability and phylogenetic relationships of African yam bean using the rbcL marker - Jacob Olagbenro Popoola; Davelyne Ifechukude Eruemulor; Oluwadurotimi Samuel Aworunse; Abiodun Sunday Oyelakin; Omena Bernard Ojuederie; Olumide Ekundayo Omotayo; Idowu Arinola Obisesan; Favour Daniel Olaoluwa (Academia Biology)
The African yam bean, AYB (Sphenostylis stenocarpa), a beneficial legume, is valuable in terms of food, nutrition, and income security. While the plant plays a crucial role in small-scale farming systems in sub-Saharan Africa, insufficient genomic data hamper the breeding potential of its germplasm. Our recent dataset based on the ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (rbcl) gene marker underscores the utility of nucleotide substitution for deciphering genetic relationships among a subset of AYB accessions. Twenty-four accessions of AYB, originating from Nigeria, Ghana, and Bangladesh, were used for this study. The rbcl gene marker reveals significant intraspecific genetic variability among AYB accessions, facilitating the delineation of distinct phylogenetic clusters that correspond to their geographic origins. The rbcl genes of the accessions were sequenced using Sanger’s technique. The obtained sequence data were analyzed using DnaSP v6.12.03, MEGA11, and descriptive statistics. Transitional base changes of C/T, T/C, A/G, and G/A varied significantly (p < 0.05) from transversion substitutions. A high gene diversity of 0.60, in addition to 13 polymorphic sites and 5 haplotypes, was recorded for the accessions. Nine accessions, including TSs 13, TSs 24, TSs 303, TSs 331, TSs 334, TSs 38, TSs 49, TSs 67, and TSs 98, had variant sequences at 531 nucleotide base positions with a variant frequency of 37.50%. The estimates of evolutionary divergence between the sequences ranged from 0.00 (TSs 4 and TSs 24) to 1.38 (TSs 1, TSs 311, and TSs 331). An analysis of the phylogenetic relationship showed a significant degree of genetic diversity with <50% bootstrap values, indicating the genetic distinctiveness of the accessions. Accessions TSs 333 and TSs 357 were the most genetically distinct accessions with a low bootstrap value of 45%. TSs 303 surprisingly had a very close relationship with the outgroup Vigna unguiculata (100%). The information presented herein could be leveraged to extend the limited genetic base of AYB through modern mutational breeding methods.